Identity Politics and Religious Minority Resilience Among Jain Communities in Contemporary India and the Global Diaspora - Muhammad Ridho (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Jainism is one of the oldest religious traditions in India and represents a small minority within the country's demographic structure. Despite constituting less than one percent of the national population, the Jain community has maintained significant socio-political influence through economic strength, philanthropic engagement, and religious leadership. The increasing influence of Hindu nationalism and cultural assimilation pressures have generated new challenges for the preservation of Jain religious identity, both within India and among diaspora communities. Therefore, understanding the strategies employed by Jains to maintain their distinctiveness has become increasingly important in contemporary studies of religion and politics. This study aims to analyse the relationship between Jainism and identity politics by examining how the Jain community negotiates minority status, preserves religious identity, and engages with socio-political structures in India and across its global diaspora. The research employs a qualitative approach using content analysis. Data were collected from academic literature, ethnographic studies, organizational reports, demographic statistics, policy documents, and contemporary media sources. The collected data were analysed through thematic interpretation focusing on minority religious resilience, cultural preservation, soft power strategies, and transnational networks. The findings reveal that the Jain community maintains its socio-political relevance through strategic political engagement, economic influence, philanthropic activities, monastic leadership, and diaspora-based transnational networks. Furthermore, digital media, youth engagement, and interfaith collaborations have strengthened Jain identity preservation amid increasing pressures of assimilation and religious homogenization. The study recommends strengthening educational initiatives, digital religious literacy, and transnational cooperation to ensure the sustainability of Jain identity in contemporary society.